Pengaruh Rasio Profitabilitas, Rasio Leverage dan Firm Size Terhadap Return Saham Perusahaan Food and Beverage Yang Terdaftar Di Bursa Efek Indonesia Periode 2017-2019 - Dela Yumei Sartika; Muhammad Ridwan Basalamah; Khalikussabir Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
Abstract This study aims to determine the effect of Profitability Ratio, Leverage Ratio, and Firm Size on Stock Return. The population in this study are Food and Beverage companies listed on the Indonesia Stock Exchange. The sample selection in this study using purposive sampling technique. The number of samples used was 12 companies. The analysis technique used in this research is multiple linear regression analysis techniques.The results of this study indicate that (1) Profitability Ratio, Leverage Ratio and Firm Size simultaneously have an effect on Stock Return (2) Profitability Ratio partially has a positive and significant effect on Stock Return (3) Partially Leverage Ratio has a positive and significant effect on Stock Return (4) Partially Firm Size has a positive and insignificant effect on Stock Returns Keyword: Profitability, Leverage, Firm Size, Stock Returns